Knowledge management in continuous product innovation: a contingent approach. (1st January 2003) - Ronchi, Stefano; Chapman, Ross; Corso, Mariano
There is a growing interest in new organisational forms and integrated managerial and technological approaches supporting companies in continuously innovating their products and processes to survive in a turbulent environment. Successful product innovation will more and more depend upon a company's ability to manage knowledge and integrate a growing number of competencies within and outside the organisational boundaries. These abilities require a complex set of interrelated managerial, technological and organisational conditions that must be designed according to the individual firm's characteristics. This paper aims to identify and analyse the relation between individual firms' contingent variables and managerial approaches to foster knowledge management in product innovation. Evidence is based on a survey of 70 companies, including European and Australian firms, developed within the Euro-Australian cooperation project entitled CIMA (Continuous Improvement for global innovation management).